2014
DOI: 10.1155/2014/108913
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Potential ofAspergillus japonicusLAB01: Production, Partial Purification, and Characterisation of an Extracellular Lipase

Abstract: Lipolytic potential of Aspergillus japonicus LAB01 was investigated by describing the catalytic properties and stability of a secreted extracellular lipase. Enzyme production was considered high under room temperature after 4 days using sunflower oil and a combination of casein with sodium nitrate. Lipase was partially purified by 3.9-fold, resulting in a 44.2% yield using ammonium sulphate precipitation (60%) quantified with Superose 12 HR gel filtration chromatography. The activity of the enzyme was maximise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…A significant ( p < 0.00015) enhancement in lipase activity, as shown by the combinatorial influence of nitrogen supplements, could be attributed to improved metabolism of the fungus in the presence of accessory growth factors, vitamins and amino acids supplied by tryptone. Souza et al reported that a combination of casein and sodium nitrate led to increased lipase production from Aspergillus japonicus LAB01 in medium supplemented with sunflower oil (1%, v/v).…”
Section: Discussionmentioning
confidence: 99%
“…A significant ( p < 0.00015) enhancement in lipase activity, as shown by the combinatorial influence of nitrogen supplements, could be attributed to improved metabolism of the fungus in the presence of accessory growth factors, vitamins and amino acids supplied by tryptone. Souza et al reported that a combination of casein and sodium nitrate led to increased lipase production from Aspergillus japonicus LAB01 in medium supplemented with sunflower oil (1%, v/v).…”
Section: Discussionmentioning
confidence: 99%
“…The purification result of the lipase using Sepharose CL-6B in this study is comparable with those using other gel filtration matrices. For example, purification of lipase from Geobacillus thermodenitrificans using Sephadex G-100 is 34-fold higher than the crude extract ( Balan et al., 2012 ), while purification of lipase from Aspergillus japonicus using Superose 12 H is 4-fold higher than the crude extract ( Souza et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme activity was measured by monitoring spectrophotometrically the increase in absorbance at 410 nm, produced by the release of p -nitrophenol (pNP) in the hydrolysis of p -nitrophenylpalmitate (pNPP). For the hydrolytic assay, the substrate solution was prepared by mixing 1 mL of solution A (90 mg of pNPP dissolved in 30 mL 2-propanol) and 9 mL of solution B (90 mM Tris-HCl buffer (pH 8.0); 2.0% Triton X-100; and 0.2% gum arabic) [ 37 ]. All analyses were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%